Cation‐/Anion‐Based Electrochemical Degradation and Rejuvenation of Electrochromic Nickel Oxide Thin Films. Issue 22 (5th September 2018) - Qu, Hui‐Ying; Primetzhofer, Daniel; Qiu, Zhen; Österlund, Lars; Granqvist, Claes G.; Niklasson, Gunnar A.
Abstract: Ni oxide thin films are widely used in electrochromic (EC) devices with variable throughput of visible light and solar energy. However, the mechanisms underlying the optical modulation – and its degradation under extended operation and subsequent rejuvenation – are poorly understood especially for Li + ‐conducting electrolytes. Here, we report a comprehensive study of the EC properties of sputter‐deposited Ni oxide films immersed in an electrolyte of LiClO4 in propylene carbonate. Cyclic voltammetry and optical transmittance measurements were used to document degradation and subsequent potentiostatic rejuvenation. X‐ray diffraction did not show evidence for accompanying changes in crystallinity, whereas vibrational spectroscopy indicated that degraded films had carbonaceous surface layers. Time‐of‐flight elastic recoil detection analysis demonstrated that both Li + and Cl‐based ions participate in the electrochromism and its degradation and rejuvenation. A major result was that degradation is associated with a reduced difference in the concentrations of Li + and Cl‐based ions in the nickel oxide during extended electrochemical cycling, and rejuvenation of degraded films is achieved by removal of Li + ions and accumulation of Cl‐based anions to regain their initial concentration difference. Our work provides new insights into the use of ion‐exchange‐based devices incorporating nickel oxide. Abstract : Bring back to life : Degradation under extended ion insertion/extraction in nickel‐oxide‐based films immersed in a lithium‐based electrolyte is associated with a reduced difference in the concentration of Li + and Cl‐based ions. Rejuvenation of degraded films can be achieved through the electrochemical removal of Li + and accumulation of Cl‐based ions to regain their initial concentration difference. This work provides new insights into the use of nickel‐oxide‐based ion‐exchange devices.